Phytochemical, antioxidant and cytotoxic activities of white mulberry (morus alba l.) from Kampung Tudan, Ranau, Sabah - Centhyea (2023)
Morus alba Linnaeus (M. alba), also commonly known as white mulberry, belongs to the genus Morus of the Moraceae family. M. alba has been widely reported for its abundant phytochemical components and promising biological activities, including antioxidant and anticancer activities. However, the variation of maturity levels, and extraction solvents could influence their phytochemicals and pharmacological activities. Regrettably, Sabah-cultivated M. alba is mainly consumed as fruits without knowing its antioxidant activity, phytochemical components, and anticancer activity. All of these have critically hindered its nutraceutical potential as antioxidant agent and pharmaceutical potential as anticancer agent against breast cancer that is the highest death-causing cancer in Sabah, Malaysia and Worldwide. Therefore, the antioxidant activity, phytochemical components and anticancer activity of Sabah-cultivated M. alba under the influence of maturity levels and extraction solvents was studied. Sabah-grown M. alba fruits (brackish black fully and ripe red mature) and leaves (young and mature) were picked as samples. They were freeze-dried before extracted in 70% (v/v) methanol (MeOH), 60% (v/v) ethanol (EtOH), and 65% (v/v) acetone. Samples were analysed for their antioxidant activity, phytochemical components’ values, and cell viability activity against the human breast cancer cell line (MCF-7). As a result, data from fruits demonstrated maturity-dependent increment for antioxidant activities, total phenolic content (TPC), total flavonoids content (TFC), and total anthocyanin content (TAC). This was indicated by the higher values in brackish black fully ripe fruits than in red mature fruits. The overview from principal component analysis (PCA) of fruits displayed brackish black fully ripe fruits in 65% (v/v) acetone as the best source of antioxidants, phenolics, and flavonoids, whereas their 60% (v/v) EtOH was the best anthocyanin source. While the red mature fruits in 65% (v/v) acetone were the best chlorogenic acid source, and their 70% (v/v) MeOH was the best rutin source. Moreover, the cytotoxicity of fruits against MCF-7 decreased across fruit maturity as the red mature fruits in 70% (v/v) MeOH exerted the strongest cytotoxicity (IC50 = 26.83 mg/mL). In leaves, data revealed maturity-dependent decrements for antioxidant activities, TPC, TFC, chlorogenic acid, and rutin. This was shown by their higher values in young leaves than in mature leaves. The overview of PCA of leaves presented young leaves in 65% (v/v) acetone as the best antioxidant sources as well as phenolics, flavonoids, and rutin sources. Though its 60% (v/v) EtOH is the best source of chlorogenic acid. Conversely, the cytotoxicity of leaves showed a maturity-dependent increment as mature leaves in 60% (v/v) EtOH possessed the strongest cytotoxicity against MCF-7 (IC50 = 2.45 mg/mL). Overall, Sabah-grown M. alba possesses significant antioxidant activity, a high amount of phytochemical components, and cytotoxic activities, which are significantly influenced by maturity levels and extraction solvents. This suggests its potential use in the functional food and pharmaceutical industries. Future studies should be focused on the screening and isolation of compounds responsible for the antioxidant and anticancer activities of M. alba fruit and leaves. Also, the cytotoxicity of the fruit and leaves should be tested on normal breast cell including the luminal epithelial cells and myoepithelial cells of breast to ensure the non-toxicity of M. alba towards them before moving on to in vivo and clinical trials.